Anesthesia and Cancer, Friend or Foe? A Narrative Review - Montejano, Julio; Jevtovic-Todorovic, Vesna (Frontiers in Oncology, 2021)
Cancer remains the leading cause of death worldwide with close to 10 million deaths reported annually. Due to growth in our aging population, it is predicted that cancer cases diagnosed between now until 2035 is to reach 24 million individuals, a staggering increase in a short time. For many solid tumors, surgical resection along with chemotherapy is the best available approach to a potential cure leading to almost 80% of cancer patients undergoing at least one surgical procedure during their disease. During surgery, the exposure to anesthesia can be lengthy, complex and often involves various modalities questioning the role, if any, anesthesia may play in recurrence or metastatic conversion. Many components of the stress and inflammatory responses can contribute to cancer growth and invasion. The agents used to induce and maintain general anesthesia have variable interactions with the immune and neuroendocrine systems and can influence the stress response during surgery. Thus, debating the best type of anesthesia that would help to attenuate sympathetic and/or pro-inflammatory responses while modulating cytokine release and transcription factors/oncogenes remains at the forefront. This may affect inducible cancer cell survival and migratory abilities not only intra-operatively, but also during the immediate post-operative period. Two major approaches should be considered, i.e., regional and general anesthesia as well as the various hypnotics, analgesics and sympatholytics commonly used. In this review, we will address the latest information as to the role that anesthesia may play during cancer surgery with specific focus on recurrence and metastasis.